A Review of High-Energy Density Lithium-Air Battery Technology: Investigating the Effect of Oxides and Nanocatalysts. (12th March 2022) - Suryatna, Asep; Raya, Indah; Thangavelu, Lakshmi; Alhachami, Firas Rahi; Kadhim, Mustafa M.; Altimari, Usama S.; Mahmoud, Zaid H.; Mustafa, Yasser Fakri; Kianfar, Ehsan
Abstract : In vehicles that require a lot of electricity, such as electric vehicles, it is necessary to use high-energy batteries. Among the developed batteries, the lithium-ion battery has shown better performance. This battery has an energy density of 10 equal to that of a lithium-ion battery and uses air oxygen as the active material of the cathode and anode like a lithium-ion battery made of lithium metal. The cathode used in these batteries must have special properties such as strong catalytic activity and high conductivity, and nanotechnology has greatly helped to improve the materials used in the cathode of lithium-air batteries. The importance of proper catalyst distribution and the relationship between the oxide product and the catalyst and the indirect effect of the ORR catalyst on the OER reaction is not present in the fuel cell. The maximum capacity of lithium-air battery theory using graphene under optimal electron conduction conditions and the experimental maximum obtained for graphene by optimizing the structure geometry, examples of structural engineering using carbon fiber and carbon nanotubes in cathode fabrication with the ability to perform the reaction properly while providing space for lithium oxide placement, are examined. This article describes the mechanism of this battery, and its components are examined. The challenges of using this battery and the application of nanotechnology to solve these challenges are also discussed.